PENINGKATAN KEMAMPUAN BINA DIRI DENGAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK ANAK TUNAGRAHITA RINGAN KELAS II SEMESTER 2 DI SLB - Yulianti Yulianti; Wiwik Dwi Hastuti; Saichudin Saichudin (Universitas Negeri Malang, 2014)
The research aimet at describing: (1) the implementation of picture and picture learning model in improving self-help ability for mild mental retardation student in the 2nd Grade Semester 2 SLB Sari Wiyata Wlingi, (2) the activity of mild mental retardation student in the 2nd Grade Semester 2 SLB Sari Wiyata Wlingi in the self-help learning with picture and picture learning model and (3) the implementation of picture and picture learning model that can improve self-help ability for mild mental retardation student in the 2nd Grade Semester 2 SLB Sari Wiyata Wlingi. This research result shows that the implementation of self-help learning with picture and picture learning model can improve student self-help ability in the 2nd Grade Semester 2 SLB Sari Wiyata Wlingi Blitar Regency. It is proven by the average value of self-help ability in the pre-action with value of 64, cycle I with the value of 77, and cycle II with the value of 81. Self-help ability passing (completeness) in the pre-action is 33%, in the cycle I for 67%, and in the cycle II for 83%. Self-help ability in the 2nd Grade of mental retardation has an improvement in each cycle. Tt can be concluded that the implementation of picture and picturelearning model can improve self-help ability to the mild mental retardation children in the 2nd Grade Tujuan dari penelitian ini adalah (1) mendeskripsikan penerapan gambar dan model pembelajaran picture, (2) untuk menggambarkan aktivitas ringan siswa retardasi mental dan (3) untuk menjelaskan pelaksanaan gambar dan model pembelajaran gambar yang dapat meningkatkan kemampuan self-help untuk ringan siswa retardasi mental di kelas 2 Semester 2 SLB Wiyata Sari Wlingi. PTK ini menunjukkan bahwa penerapan kemampuan Self-help di kelas 2 keterbelakangan mental memiliki peningkatan setiap siklus, dalam siklus I untuk 67%, dan pada siklus II 83%. Oleh karena itu, dapat disarankan bagi guru untuk menggunakan gambar dan gambar model pembelajaran dalam pembelajaran self-help dalam rangka meningkatkan kemampuan self-help siswa